Odpowiedzi

2010-04-12T21:25:43+02:00
12b+9= 3(4b+3)
42-4b=4(10,5-b)
22b+6=4(5,5b+1,5)
0,4-0,2b= 2(0,2-0,1b)
1/6b+5/6=1/6(b+5)
20b+6c=4(5b+1,50
1,4a-7=7(0,2a - 1)
0,9b+12= 3(0,3b+4)
1,6a-2,4c= 8(0,2a-0,3)
2,5a+0,5b= 5(0,5a+0,1b)

2010-04-12T21:26:24+02:00
12b+9= 3(4b+3)
42-4b=2(21-2b)
22b+6= 2(11b+3)
Najlepsza Odpowiedź!
2010-04-12T21:38:55+02:00
12b+9=3(4b+3)
42-4b=4(10,5-b)
22b+6=4(5,5b+1,5)
0,4-0,2b=0,2(2-1b)
1/6b+5/6=1/6(b+5)
20b+6c=4(5b+1,5c)
1,4a-7=7(0,2a-1)
0,9b+12=3(0,3b+4)
1,6a-2,4c=4(0,4a-0,6c)
2,5a+0,5b=5(0,5a+0,1b)